Financial Recordkeeping: Organizing Your Financial Life - Selena Garrison; Michael S. Gutter; Julie England; Josephine Turner; Nayda Torres (EDIS)
Revised! FCS5205, a 4-page fact sheet by Selena Garrison, Michael S. Gutter, Julie England, Josephine Turner, and Nayda Torres, addresses what financial and personal documents individuals should keep and why, how long they should be kept, and where they should be stored. Published by the UF Department of Family Youth and Community Sciences, October 2009.